Reliability and validity of Chengdu pediatric emergency triage criteria: case study of a single center in China - Yingying Zhao; Liqing He; Juan Hu; Jing Zhao; Xiaolan Yi; Humin Huang (BMC Pediatrics, 2023)
Abstract Background We aimed to examine the reliability and validity of Chengdu pediatric emergency triage criteria in order to provide a reference for the development of pediatric emergency triage within other hospitals. Methods We developed Chengdu pediatric emergency triage criteria based on the conditions/symptom, vital signs, and the Pediatric Early Warning Score system within our hospital using the Delphi method in 2020. The simulation scenario triage and real-life triage which were conducted in our hospital during January - March 2021, and the retrospective study of triage records extracted from our hospital’s health information system in February 2022, were used to measure the agreement in triage decisions between the triage nurses, and between the triage nurses and the expert team. Results For the 20 simulation cases, the Kappa value of triage decisions between the triage nurses was 0.6 (95% CI 0.352–0.849), and the Kappa value of triage decisions between the triage nurses and the expert team was 0.73 (95% CI 0.540–0.911). For the 252 cases in the real-life triage, the Kappa value of triage decisions between the triage nurses and the expert team was 0.824 (95% CI 0.680–0.962). For the 20,540 cases selected for the retrospective study of triage records, the Kappa value of triage decisions between the triage nurses was 0.702 (95% CI 0.691–0.713); that between Triage Nurse 1 and the expert team was 0.634 (95% CI 0.623–0.647); and that between Triage Nurse 2 and the expert team was 0.725 (95% CI 0.713–0.736). The overall agreement rate in triage decisions between the triage nurses and the expert team in the simulation scenario triage was 80%; that between the triage nurses and the expert team in the real-life triage was 97.6%; and that between the triage nurses in the retrospective study was 91.9%. In the retrospective study, the agreement rates in triage decisions between Triage Nurse 1 and the expert team, and between Triage Nurse 2 and the expert team, were 88.0% and 92.3%, respectively. Conclusion Chengdu pediatric emergency triage criteria that developed within our hospital is reliable and valid, and can promote rapid and effective triage by triage nurses.